South Caucasus and Central Asia - The Belt and Road Initiative : Uzbekistan Country Case Study - World Bank (World Bank, Washington, DC, 2020)
Uzbekistan is a resource-rich country with a relatively young population of 33 million, the largest in Central Asia. It is also a geographic pivot for the region, bordering all other Central Asian countries and Afghanistan, with transit connections in all directions. As a double landlocked country, it is uniquely dependent on these cross-border transport connections and on how well they work. It can also potentially be the largest market in Central Asia and given its sizeable young labor force and substantial agricultural and manufacturing capacity, a major regional exporter. This note attempts to highlight the potential economic impact of BRI on the Tajik economy. It looks at how, if fully implemented globally, the BRI is expected to achieve better transport connections and greater economic integration of participating BRI countries, discusses improvements in Tajikistan’s cross-border transport, electricity and ICT infrastructure to-date, and assesses the potential impact of the completion of all BRI transport projects on Tajik shipment time. It further looks at the likely economic impact of BRI reductions in shipment time on exports, FDI and GDP, and the spatial distribution of benefits within the country and at how complementary polices can enhance the positive impact and mitigate risks. Finally, it examines the fiscal risk of Tajikistan’s scaling-up of investment in BRI transport projects in the coming years without undermining medium-term debt sustainability.